Development of an instrument for measuring adolescent health compromising behaviours among rural students: a Delphi study - Mandal, Kasturi; Mandal, Pankaj K. (International Journal Of Community Medicine And Public Health, 2020)
Background: There is an increasing trend of health compromising behaviors in adolescents worldwide. As behavioral determinants are extremely culture specific, person specific and as such least instruments have been developed in West Bengal. The aim of this study was to develop a specific instrument with strong content validity for measuring adolescent health compromising behavior of adolescent students of rural area. Methods: Face and content validity were evaluated in three round Delphi procedure by a panel of 15 experts who had extensive experience and knowledge of adolescent health compromising behavior. To ensure good cultural fit of the instrument with the rural context, modified Delphi procedure conducted among five stakeholders: medical and nursing, psychologist, sociologist, education experts, and parents. Reliability testing done among 100 students through test retest method with one-week interval. Results: A 85 questions-based instrument was developed reflecting 5 areas of health compromising behaviors; physical inactivity, sedentary behavior, unhealthy eating, poor dental hygiene, tobacco use and their multi-dimensional correlates. After round 3 Delphi, the final instrument had overall S–CVI/Ave of 99.05% and found to be reliable as evident by Pearson product moment correlation coefficient (r) for the scoring questions ranged from 0.72 to 0.84 and Cohen’s kappa coefficient (k) for nominal data, ranged from 0.8-1. Conclusions: The instrument has similarities as well as differences compared with instruments of Western origin. The instrument was valid and reliable and can be applied in both research and practice for measuring adolescent health compromising behaviors.